Contribution of 18 F-fluorocholine PET-CT to the preoperative localisation of parathyroid adenoma for the treatment of primary hyperparathyroidism - Suzanne Garnier; Clémentine Mahéo; Gael Potard; Marie-Béatrice Cavarec; Nathalie Roudaut; Philippe Thuillier; Rémi Marianowski; Ronan Abgral; Jean-Christophe Leclere (Scientific Reports)
Abstract 18 F-fluorocholine PET-CT is considered a second-line method for the preoperative localisation of parathyroid adenomas in primary hyperparathyroidism. The aim was to compare the diagnostic performance of 18 F-fluorocholine PET-CT and standard imaging modalities in the preoperative localisation of parathyroid adenomas in primary hyperparathyroidism. The primary objective was to assess the performance of 18 F-fluorocholine PET-CT in cases of negative or discordant standard imaging. The secondary objective was to evaluate the diagnostic performance of both 18 F-fluorocholine PET-CT and standard imaging in relation to patient characteristics. We conducted a retrospective, monocentric study, including 156 patients who underwent parathyroidectomy between 2017 and 2023. All patients underwent preoperative 18 F-fluorocholine PET-CT and had an indication for surgery due to primary hyperparathyroidism. A total of 156 patients were included in the study, the majority of whom were women (78%). Seven patients had multigland disease (4.49%). Sensitivity was 60.14% for cervical ultrasound, 46.21% for [99mTc]-MIBI scintigraphy, and 95.97% for 18 F-Fluorocholine PET-CT. 18 F-Fluorocholine PET-CT showed a higher sensitivity than cervical ultrasound and [99mTc]-MIBI scintigraphy, especially for multiple parathyroid adenomas (100, 57.14, and 42.86%, respectively). Univariate analysis showed better results for cervical ultrasound in men (p = 0.005). Larger adenomas showed better performance on [99mTc]-MIBI scintigraphy (p = 0.026), and elevated PTH levels were associated with significantly worse performance on 18 F-fluorocholine PET-CT (p = 0.023). Multivariate analysis showed that scintigraphy performance was worse in the presence of thyroid nodules (p = 0.049, RR = 2.046, 95% CI 1.005–4.166). 18 F-fluorocholine PET-CT is a valuable imaging modality for the preoperative localisation of parathyroid adenomas in primary hyperparathyroidism, with superior performance compared to conventional imaging modalities. [99mTc]-MIBI scintigraphy showed reduced diagnostic performance in the presence of thyroid nodules.